A new socio-rational secret sharing scheme. (2017) - Jin, Jianghao; Zhou, Xie; Ma, Chuangui; Wang, Xu'an
We introduce the concept of a socio-rational secret sharing scheme, in which shares are delivered based on players' reputation and the way they contact with other participants. At the secret sharing stage, weights of players are defined such that participants who cooperate will get more shares than those who defect. Alternatively, a newcomer can be enrolled in the scheme when a corrupted player is disengaged immediately. In other words, this scheme successfully renews shares at each cycle without changing the secret, and it allows trusted participants to have a chance to obtain more authority. Our intention is that, in real world applications, participants of a secure scheme may have different levels of importance (i.e., the weight of shares a player owns) as well as reputation (i.e., cooperation with other players for the share renewal or secret recovery). Therefore, a good scheme should balance these two factors alone. In the proposed schemes, both the traditional and rational players are considered in an unconditionally secure setting.